2021
DOI: 10.1093/intimm/dxab016
|View full text |Cite
|
Sign up to set email alerts
|

1′-Acetoxychavicol acetate inhibits NLRP3-dependent inflammasome activation via mitochondrial ROS suppression

Abstract: The nucleotide-binding oligomerization domain-like receptor (NLR) family pyrin domain containing (NLRP) 3 inflammasome is a multiprotein complex that triggers Caspase-1-mediated IL-1β production and pyroptosis, and its dysregulation is associated with the pathogenesis of inflammatory diseases. The 1′-acetoxychavicol acetate (ACA) is a natural compound in the rhizome of tropical ginger Alpinia species with anti-microbial, -allergic, and -cancer properties. In this study, we found that ACA suppressed NLRP3 infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…10,11 Meanwhile, pyroptosis is a programmed cell death which is majorly regulated by caspase 1. 12,13 In addition, caspase 1 is often upregulated when the growth of NSCLC cells is inhibited, suggesting that the promotion of pyroptosis might be associated with the progression of NSCLC. 14 Therefore, it is necessary to investigate the correlation between hsa_circ_0000729 and pyroptosis in NSCLC cells with the purpose of exploring new effective strategies against NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Meanwhile, pyroptosis is a programmed cell death which is majorly regulated by caspase 1. 12,13 In addition, caspase 1 is often upregulated when the growth of NSCLC cells is inhibited, suggesting that the promotion of pyroptosis might be associated with the progression of NSCLC. 14 Therefore, it is necessary to investigate the correlation between hsa_circ_0000729 and pyroptosis in NSCLC cells with the purpose of exploring new effective strategies against NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…e nonpolar extracts of the rhizomes reported many types of plant sterols such as stigmasterol, β-sitosterol and several closely related phenylpropanoids such as ACA and 1′-acetoxyeugenol acetate (AEA). ACA being the major phytoconstituent of the plant, has been widely investigated for its pharmacological activities which include antiallergy, anti-inflammatory, antiulcer, antiviral and antitumour [67][68][69].…”
Section: ′-Acetoxychavicolmentioning
confidence: 99%
“…Emerging evidence has suggested that mtDNA serves a key role in activating the NLRP3 inflammasome. Sok et al ( 50 ) revealed that inhibiting release of oxidative mtDNA decreased generation of mitochondrial ROS and inhibited activation of NLRP3 inflammasomes. Severe fever with thrombocytopenia syndrome caused by viral infection can also cause the release of oxidative mtDNA and activate the NLRP3 inflammasome, leading to intensive inflammation ( 51 ).…”
Section: Effect Of Mtdna On the Occurrence And Development Of Sirsmentioning
confidence: 99%